Effects of smartphone addiction on cognitive function and physical activity in middle-school children: a cross-sectional study - Al-Amri, Ahlam; Abdulaziz, Sahar; Bashir, Shahid; Ahsan, Mohammad; Abualait, Turki (Frontiers in Psychology, 2023)
This study aimed to investigate the effects of smartphone addiction on cognitive function and physical activity in middle-school children. The population of 196 children (male and female) from middle schools have recruited in this study with an average age of 12.99±0.81 years, the height of 153.86±6.50 meters, weight of 48.07±7.31 kilograms, and body mass index of 20.22±2.08 kg/m2. Smartphone addiction was determined using Arabic versions of the Smartphone Addiction Scale Short Version, and physical activity levels were assessed by a physical activity questionnaire for older children. The working memory and selective attention domains of cognitive function were evaluated using a laptop's digital version of the memory automaticity and Flanker tasks, respectively. A one-way MANOVA was conducted to determine the differences in working memory between the smartphone-addicted and non-addicted groups. The Pearson Chi-squared test was used to look at how smartphone addiction affects physical activity. The cognitive function- attention domain accuracy component showed a statistically significant difference between the groups, with a (p=0.05). The reaction time between smartphone-addicted and non-addicted children showed no statistically significant difference (p=0.817). The relationship between smartphone addiction and physical activity was statistically significant (p<0.001). Inter-action effects between physical activity and smartphone addiction on reaction times showed statistically insignificant (p= 0.250) differences. The non-addicted children had significantly higher physical activity levels than addicted children; smartphone addiction reduced physical activity. This study indicated that physical activity's effect on reaction times did not depend on smartphone addiction levels